(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
As we know, the coefficient of variation (CV) is one of the main quality indexes in the electronic testing for raw silk. Therefore, to study the classification of this index, it’s nessary to get the distribution and other statistical information of this variable. In our previous study, we have gotten its distribution when the population is normal and the sampling is random. However, in the real testing, the CV value is obtained by computing a series of continuous silk size tested by the electronic machine. Due to the continuity of the silk filament, the series of raw silk size can be regarded as a continuous sample. The characteristics of the size from the continuous sample will be different from that of the random sample. This paper analyzes the results of the continuous sampling tests of the CV of the raw silk size, and deduces the distribution of CV of the raw silk size and its characteristics in the case of continuous sampling test, which provides a theoretical basis for the development of electronic testing standard.